2019
DOI: 10.1007/s10840-019-00680-2
|View full text |Cite
|
Sign up to set email alerts
|

State of the art: leadless ventricular pacing

Abstract: Background Cardiac pacing has been shown to improve quality of life and prognosis of patients with bradycardia for almost 60 years. The latest innovation in pacemaker therapy was miniaturization of generators to allow leadless pacing directly in the right ventricle. There is a long history and extensive experience of leadless ventricular pacing in Austria. However, no recommendations of national or international societies for indications and implantation of leadless opposed to transvenous pacing systems have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Although the proportion of right ventricular pacing was less than 1%, the patient showed good clinical response to pacemaker therapy as there was no recurrence of syncope since beginning of treatment. Possible treatment strategies (generator change vs. TPS implantation) were discussed with the patient, and we decided to opt for a TPS according to current recommendations [ 7 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Although the proportion of right ventricular pacing was less than 1%, the patient showed good clinical response to pacemaker therapy as there was no recurrence of syncope since beginning of treatment. Possible treatment strategies (generator change vs. TPS implantation) were discussed with the patient, and we decided to opt for a TPS according to current recommendations [ 7 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Importantly, the potential benefits of LCPs must be confronted with the limited data on the long-term follow-up, and also the procedure of device replacement or retrieval is still debated. 34 According to a national expert consensus document of the Austrian Society of Cardiology, LCP retrieval should not be recommended as a routine procedure and should be limited only to specific issues, ie, endocarditis or system upgrades. 34 One worldwide experience of 40 successful device retrievals revealed that it may be feasible and safe if performed with a special sheath and a snare catheter and introduced via femoral access.…”
Section: Leadless Cardiac Pacemakersmentioning
confidence: 99%
“…34 According to a national expert consensus document of the Austrian Society of Cardiology, LCP retrieval should not be recommended as a routine procedure and should be limited only to specific issues, ie, endocarditis or system upgrades. 34 One worldwide experience of 40 successful device retrievals revealed that it may be feasible and safe if performed with a special sheath and a snare catheter and introduced via femoral access. The most common reasons for extraction included elevated pacing threshold, endovascular infection, and indications for a system upgrade to a transvenous device.…”
Section: Leadless Cardiac Pacemakersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a small capsule with a single chamber (VVI) PM system implanted in the right ventricle, usually via a transfemoral catheter (Figure 6). Leadless PMs have a lower rate of displacement, less torque, and less heating than conventional PMs due to their small size and the absence of a lead 45,46 (Figure 7). The Micra System and all leadless PMs are MR conditional at 1.5 and 3 T. 47,48…”
Section: Leadless Pmsmentioning
confidence: 99%